2023
DOI: 10.1002/mnfr.202200906
|View full text |Cite
|
Sign up to set email alerts
|

Improving In Vitro Detection of Sensitization to Lipid Transfer Proteins: A New Molecular Multiplex IgE Assay

Balsells‐Vives Sara,
Flügge Ulrike,
Brix Bettina
et al.

Abstract: Scope: LTP-syndrome is characterized by sensitization (IgE) to multiple non-specific lipid transfer proteins (nsLTPs) with a variable clinical outcome. The treatment is primarily based on offending food avoidance. However, the determination of Pru p 3-specific IgE is currently the main diagnostic tool to assess sensitization to nsLTPs. Herein, the study evaluates improvement of LTP-syndrome diagnosis and clinical management using a new IgE multiplex-immunoblot assay with a high diversity of food nsLTPs. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…It was observed that there was a positive correlation between the sIgE levels of the single allergen components (Pru p 3, Mal d 3, Ara h 9, Cor a 8 and Jug r 3) with respect to the sIgE levels of the ImmunoCAP. This new IgE multiplex-immunoblot LTP assay showed a good diagnostic performance allowing the culprit food allergies assessment [38]. Another study evaluated the ImmunoCAP and the EUROLINE system for the sensitization profiles towards egg white, yolk extract with the allergen components Gal d 1, 2, 3, 4.…”
Section: Allergen-specific Ige In Vitro Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that there was a positive correlation between the sIgE levels of the single allergen components (Pru p 3, Mal d 3, Ara h 9, Cor a 8 and Jug r 3) with respect to the sIgE levels of the ImmunoCAP. This new IgE multiplex-immunoblot LTP assay showed a good diagnostic performance allowing the culprit food allergies assessment [38]. Another study evaluated the ImmunoCAP and the EUROLINE system for the sensitization profiles towards egg white, yolk extract with the allergen components Gal d 1, 2, 3, 4.…”
Section: Allergen-specific Ige In Vitro Testingmentioning
confidence: 99%
“…Milk [56] High throughput Need to improve the Sesame [32] Hazelnut [33] Peanut allergic children [35] Kiwi [36] LTP (Multiple Food) [38] Egg white and yolk [39] Standardized High throughput Can be automatized Poor in detection of sensitization from clinically reactive FA.…”
Section: T Cells Peanut [55]mentioning
confidence: 99%